Gastroenteritis in Patients Hospitalized at the Pediatric Ward of Dr. Pirngadi Hospital Medan - Gustina Lubis; Tm. Thaib; Atan Baas Sinuhaji; A. H. Sutanto (Indonesian Pediatric Society, 1992)
In 1989, oj2350 patients hospitalized in the paediatric ward of Dr. Pirngadi Hospital, Medan, 829 (35.3%) were gastroenteritis cases, with male more than female. Most of the patients with gastroenteritis were found in the age group of under 1 years (521 cases = 62.8%). The highest prevalence was found in january, February and March. Mild, moderate and severe dehydration were encountered in 2. 7%, 83.1% and 14.2% cases respectively. Eighty for (10.1%) cases had been treated with oralit before admission. Only 49. 1% of those patients with gastroenteritis under two years of age were breastfed. The patients of under five year old were 791 (95. 4%) cases; 259 (32. 7%) cases were malnourished. The overall mortality rate of these patients with gastroenteritis was 5.9% ( 49 cases). The age specific mortality rate was highest in the age group of 6- 12 months. Usually patients died with gastroenteritis had complications or associated diseases.